HUBUNGAN ANTARA KONFLIK PERAN GANDA WANITA DENGAN KINERJA GURU PENDIDIKAN ANAK USIA DINI (PAUD) GUGUS MAWAR KECAMATAN BANGKINANG KABUPATEN KAMPAR - Wekaningtyas Andalas Andalas; Daviq Chairilsyah Chairilsyah; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to describe the double role conflict early childhood teacher of Gugus Mawar in Bangkinang distric; to knowing the performance of early childhoot teachers of Gugus Mawar in Bangkinang district; to determine the relationship of conflict with the perfoemance of the double role of early childhoot teachers of Gugus mawar bangkinang district. The benefits of this research is to give input to edicational pracitioners, especially the manager of educators in order to make early childhoot teacher training programs continuously. In terms of theoretical provide an understanding of the conflict based on their experiences, for teachers to be able manage conflict in a positive double role, improfing the performance of early childhoot teachers. The population in this study were all early childhoot teachers of Gugus Mawar in Bangkinang district kampar, which consists of teachers who have a family (husband and children have), as many as 40 teachers. The samples are saturated sample the entire population involved. Overview conflict double role of early childhoot teachers of Gugus Mawar in Bangkinang district is at the low category.in view of the performance of teachers at the high categori. Early childhoot teachers of gugus mawar in bangkinang district have a high level of teacher performance and double role at low levels. Results of rhitung value of 0,109 with a p-value = 0.5 this. Therefore p> 0.05 (0.5> 0.05). we conclude there is no significant correlation between the two variables tested. This study accepts H0 means that tehre is no significant relationship between conflict with the performance of the double role of early childhood teachers Gugus Mawar of Bangkinang distric. Keywords: Dual role conflict, Teacher performance